Radiation exposure in recurrent medical imaging: identifying drivers and high-risk populations - Chen, Juan; Zheng, Jianjun; Zhang, Qun; Zhang, Jingfeng; Dai, Qi; Zhang, Dandan (Frontiers in Public Health, 2025)
Medical imaging modalities constitute indispensable diagnostic and therapeutic decision-making tools in contemporary clinical practice. These modalities are pivotal in disease detection, longitudinal monitoring, and treatment response assessment. However, the progressive accumulation of radiation exposure from recurrent imaging procedures has sparked significant clinical concerns regarding potential carcinogenic and non-carcinogenic health implications. This review analyzes the driving factors of recurrent medical imaging examinations, identifies high-risk populations, and evaluates the potential health risks associated with cumulative radiation exposure, aiming to optimize imaging techniques and dose management strategies. By integrating global radiation exposure data (e.g., UNSCEAR reports) and multicenter clinical research evidence combined with a literature review and dosimetry models, the study reveals the high-risk nature of emergency department patients, chronic disease patients, children, and female populations in recurrent imaging. Clinical needs, demographic characteristics, technological misuse, and uneven healthcare resource allocation are identified as key drivers of recurrent imaging. This review further highlights that short-term, high-frequency imaging accelerates cumulative radiation dose accumulation, potentially elevating long-term health risks, while long-term, low-dose exposure is associated with cardiovascular diseases and malignancies. Based on the linear no-threshold (LNT) model and evidence of DNA repair mechanisms, the study proposes individualized risk assessment to optimize imaging intervals and dose modulation techniques to balance diagnostic efficacy and radiation safety. The policy implications of this research include advocating for enhanced radiation safety education and targeted management strategies for high-risk populations and providing empirical support for updating international radiation protection guidelines, thereby facilitating the clinical implementation of the “As Low As Reasonably Achievable” (ALARA) principle.